The Ifo Investment Database - Thomas Strobel; Stefan Sauer; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper we present the Ifo Investment Database, which provides annual investment data for 12 investment assets in 50 German industries from 1991 onward. The data is consistent with national accounts statistics provided by the German Federal Statistical Office and is based on investments in 88 different sub-assets. This disaggregated level of information allows allocating investments by asset type to each industry, using an investment flow matrix. The database enables researchers to analyze structural investment behavior on the industry level and to identify changes in the importance of in-vestment assets. It additionally collects leasing data from the Ifo Investment Survey Leasing, which enables the conversion of the investment data from the owner to the user concept. This unique feature allows the researcher to examine changes in financing of investments. We describe the structure and methodology of the database and illustrate its variety and strengths by looking at some descriptive examples. Finally, we outline how the data can be accessed.
Keywords: E01; E22; C61; L16; 330; investment database; investment matrix; leasing; owner concept; user concept